An examination of the growth of Islamic banking in Indonesia from 2003 to 2010 - Faturohman, Taufik (Curtin University, 2013)
This research investigates the growth of Islamic banks in Indonesia, by measuring their comparative stakeholder efficiency with that of non-Islamic banks over the period 2003 to 2010. Financial and other data of the banks are analysed by applying Data Envelopment Analysis and regression analysis. This research finds significant differences between the stakeholder efficiency of the Islamic and non-Islamic banks.The findings indicate that Islamic banks should improve their stakeholder efficiency to enable to attain sustainable growth.